Challenges in the Management of Pulmonary Contusion with Multiple Rib Fractures and Associated Injuries: A Case Report - Kahar, Liliriawati Ananta (HM Publisher, 2024)
Background: Pulmonary contusion, a common consequence of chest trauma, presents significant management challenges, especially when associated with multiple rib fractures and other injuries. These cases often require intensive care due to the high risk of complications and mortality. This report presents a case of a patient with pulmonary contusion, multiple rib fractures, and cerebral contusion to illustrate the complexities involved in managing such cases. Case Presentation: A 44-year-old male was admitted to the intensive care unit (ICU) following a motor vehicle accident. He presented with decreased consciousness, multiple rib fractures, severe lung contusion, and cerebral edema. The patient's condition was further complicated by the development of respiratory distress and hemodynamic instability. Conclusions: The management of pulmonary contusion with multiple rib fractures and associated injuries requires a multidisciplinary approach with careful attention to respiratory support, hemodynamic management, pain control, and early intervention for complications.